Woman's century - Milner, Madeline Wade (My University, 1891)
Introduction: Victor Hugo says, “this is woman’s century.” It has been left to our time to realize more fully the ideal as to woman’s true place and work. Men have emphasized the thought that man was not made for woman, but woman for man, and that if he had not needed her she would not have been created. It was long thought unnecessary for a woman to have any of the education or training given to man. She was to be subject to him to be guided by him, and to lose her personality in him. As Milton says, “For contemplation he, and valor formed, For softness she, and sweet attractive grace, He for God only, she for God in him.” From the beginning of the nineteenth century woman has risen into a higher and broader field of thought and action. It is more clearly recognized now that woman has a work of her own in the world that man cannot do for her. While it may always be left to man to lead in the subjection of physical forces woman will lead in the higher reaches of moral and spiritual. In virtue of her motherhood, she is the character-builder of the race, the teacher of mankind, and to do this work she needs the broadest culture and the largest liberty. Women have made a great advance in all directions in the last one hundred years and especially in our own country.
Citation: Milner, Madeline Wade. Woman's century. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Gender roles; Women; Education; Sociology; Theses; Manuscripts (documents)